2015
DOI: 10.1016/j.neulet.2015.06.038
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic dopaminergic neurons in an animal model of seasonal affective disorder

Abstract: Light has profound effects on mood regulation as exemplified in Seasonal Affective Disorder (SAD) and the therapeutic benefits of light therapy. However, the underlying neural pathways through which light regulates mood are not well understood. Our previous work has developed the diurnal grass rat, Arvicanthis niloticus, as an animal model of SAD. Following housing conditions of either 12:12hr Dim Light:Dark (DLD) or 8:16hr Short Photoperiod (SP), which mimic the lower light intensity or short day-length of wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 39 publications
0
22
0
Order By: Relevance
“…A possible candidate would be the hypothalamic orexin/hypocretin neurons, which have been implicated in many important functions including wakefulness, energy homeostasis, emotion, and cognition (Gerashchenko and Shiromani, ; Tsujino and Sakurai, ). Our previous work in grass rats has shown that the number of orexin‐ir neurons and the density of orexin‐ir fibers are affected by lighting conditions, with higher levels of orexin‐ir in brLD than in dimLD groups (Deats et al, ); and orexin pathways mediate the effects of light on other brain regions, i.e., the dorsal raphe (Adidharma et al, ) and hypothalamic dopaminergic neurons (Deats et al, ). Orexinergic cells project directly to the hippocampus in both nocturnal laboratory rats and diurnal grass rats (Nixon and Smale, ; Peyron et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A possible candidate would be the hypothalamic orexin/hypocretin neurons, which have been implicated in many important functions including wakefulness, energy homeostasis, emotion, and cognition (Gerashchenko and Shiromani, ; Tsujino and Sakurai, ). Our previous work in grass rats has shown that the number of orexin‐ir neurons and the density of orexin‐ir fibers are affected by lighting conditions, with higher levels of orexin‐ir in brLD than in dimLD groups (Deats et al, ); and orexin pathways mediate the effects of light on other brain regions, i.e., the dorsal raphe (Adidharma et al, ) and hypothalamic dopaminergic neurons (Deats et al, ). Orexinergic cells project directly to the hippocampus in both nocturnal laboratory rats and diurnal grass rats (Nixon and Smale, ; Peyron et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In postmortem human brain tissue, the number of midbrain dopaminergic neurons is higher in those who died in summer compared to those in winter (Aumann et al, ). Our own work using Nile grass rats ( Arvicanthis niloticus ), a diurnal rodent species, shows an increased number of dopaminergic and serotoninergic neurons in animals that had been housed over 4 weeks under daytime bright light (∼1000 lux) as compared to those kept under daytime dim light (∼50 lux) (Deats, Adidharma, & Yan, ; Leach, Adidharma, & Yan, ). On the basis of these findings, we hypothesized that long‐lasting changes in the brain, beyond temporary enhancement of arousal or attention, are likely to contribute to the superior cognitive performance associated with brighter illumination.…”
Section: Introductionmentioning
confidence: 99%
“…Keeping adult diurnal rodents in a short photoperiod (such as light:darkness at 5:19 hr) for a period of time causes depression‐like behavior (Ashkenazy‐Frolinger, Kronfeld‐Schor, Juetten, & Einat, ; Leach, Adidharma, & Yan, ). When animals are entrained to 12:12 light‐dark cycles with dim light during the light‐phase, they also display depressive behavior similar to animals in a short photoperiod (Deats, Adidharma, & Yan, ; Ikeno, Deats, Soler, Lonstein, & Yan, ). If diurnal rodents are entrained to light‐dark cycles but with dim light at night, they have impaired cognition and depression without circadian alterations (Fonken, Kitsmiller, Smale, & Nelson, ).…”
Section: Melanopsin‐expressing Intrinsically Photosensitive Retinal Gmentioning
confidence: 99%
“…Whether the observed phenomena are determined by the absolute duration of daylength or the total irradiance level over the light/dark cycle (a question that bears on SAD etiology) remains unclear. Experiments with an equinoctial photoperiod using dim light in the photophase have revealed depressive effects analogous to those seen with short photoperiods (Deats et al 2015). The converse experiment, dim light at night, impairs cognition and causes depressive behavior in diurnal rodents without circadian alterations (Fonken et al 2012), whereas the same intervention in mice leads to mood deficits with attenuation of SCN rhythms (Fonken et al 2013).…”
Section: The Effect Of Light On Moodmentioning
confidence: 96%